2010
DOI: 10.1016/s1672-0229(10)60024-1
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, Identification and Comparative Analysis of Non-Specific Lipid Transfer Protein (nsLtp) Family in Solanaceae

Abstract: Plant non-specific lipid transfer proteins (nsLtps) have been reported to be involved in plant defense activity against bacterial and fungal pathogens. In this study, we identified 135 (122 putative and 13 previously identified) Solanaceae nsLtps, which are clustered into 8 different groups. By comparing with Boutrot’s nsLtp classification, we classified these eight groups into five types (I, II, IV, IX and X). We compared Solanaceae nsLtps with Arabidopsis and Gramineae nsLtps and found that (1) Types I, II a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 44 publications
8
58
0
1
Order By: Relevance
“…S1). It has been speculated that Type VII nsLTPs appeared specifically in monocots while Type IX nsLTPs were unique to dicots39, and our results in Gossypium further confirmed this viewpoint. In addition, G. arboreum lost all the Type III and Type IX nsLTPs (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…S1). It has been speculated that Type VII nsLTPs appeared specifically in monocots while Type IX nsLTPs were unique to dicots39, and our results in Gossypium further confirmed this viewpoint. In addition, G. arboreum lost all the Type III and Type IX nsLTPs (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The system categorized 267 nsLTPs into nine types (Type I-IX) based on a genome-wide analysis of rice ( Oryza sativa ), wheat ( Triticum aestivum ) and Arabidopsis thaliana . Then, nsLTPs in other plant species were also grouped according to Boutrot’s method with slight modifications49101112, and novel types such as Type X9 and Type XI4 were identified.…”
mentioning
confidence: 99%
“…This analysis allowed us to identify 4 different sequences, named LTPa, LTPb, LTPc and LTPd, which were found 3, 2, 1 and 2 times, respectively. This result is consistent with LTP1 being encoded by multiple genes, as previously reported (Botton et al, 2002;Gao et al, 2005;Liu et al, 2010;Vignols et al, 1997). In Fig.…”
Section: Sequence Analysessupporting
confidence: 93%
“…Moreover, we found that only one type VIII and very few type III/V/VI nsLtp genes existed in B. rapa (Table 1), just like those in Arabidopsis and rice [17]. A previous study demonstrated that four of the types (III/V/VI/VIII) were not identified in six Solanaceae species thus far [18]. Our results also showed that type V/VIII BrnsLtps had no duplications (Fig.…”
Section: Discussionsupporting
confidence: 69%